Customer Values and Repurchase Intention in Pasar Lama Culinary Center, Tangerang - Kevin Gustian Yulius; Annabella N. Adhitya; Jessica Valencia; Vasco A. H. Goeltom (Jurnal Pariwisata Nusantara (JUWITA), 2023)
Purpose: Pasar Lama, a culinary center located in Tangerang’s Chinatown area. This area is famous for its’ street food and exclusive food and beverage vendors. Repurchase intention in a food and beverage establishment is affected by utilitarian and hedonic values of the customer. Perceived values are also influenced by several factors, namely food quality, service quality, physical environment, price, and rapidity. Researching repurchase intention in Pasar Lama is crucial for enhancing culinary tourism's sustainability, guiding businesses, attracting more tourists, informing policies, and preserving local culture. Method: This is a quantitative explanatory research with cross-sectional data with people who visited and bought street food in Pasar Lama as the population. The sampling technique was purposive sampling with 160 respondents given online questionnaires. The data was the analyzed with SEM-PLS method using SMART-PLS v3.0. Result: The result pointing out a different conclusion than the previous study because of the difference between population. Four hypotheses were rejected on the relation of food and service quality with utilitarian value, and physical environment & price with hedonic value. Contribution: A heterogenous population in Pasar Lama and Indonesia would bring different result on influence of perceived values on repurchase intention. Different settings, time dimensions, and sampling technique are suggested for future research.